Conduct, Performance, and Dilemmas of Inter-organizational Virtual Organizing - Jha, Sanjeev; Watson-Manheim, Mary (Virtuality and Virtualization, 2007)
Firms are increasingly embedded in networks of relationships with other organizations that are of strategic importance. An organization’s participation in a network may provide access to information, resources, markets, and technologies, or it may lock it in unproductive relationships from which it may be difficult to extricate. Therefore, it is no longer adequate to analyze firms’ conduct and performance by examining firms in isolation from their network partners. Strategy research has investigated inter-organizational alliances for some time. However, the primary focus of this research has been to examine the antecedents of network formation and relatively lesser attention has been paid to the implications of alliances and networks on a firm’s performance. Since virtual organizations are conceptualized as strategic networks and alliances among organizations, we examined literature on virtual organizations to understand what has been done in inter-organizational context. We found 34 papers out of a total of 117 papers on virtual organization that examined virtual organizing at inter-organizational level. We classified each of the short-listed papers by virtual organizing type (network membership, network structure, tie modality, and time-frame), performance, and dilemmas of virtual organizing. Our analyses showed that inter-organization virtual organizing strategy varied with the goals of virtual organizing. Across the short-listed papers we found a pattern of organizing that depended on whether organizing was for abstract resources (knowledge, skills, competencies, etc.) or for specific goals (outsourcing key components). Virtual organizing for abstract resources tended to exhibit decentralized network structure and collaborative ties with partners, while virtual organizing for specific goals tended to exhibit centralized network structure and opportunistic ties. We found a lack of empirical literature examining the process of inter-organization virtual organizing strategy and its consequences.